Analisis Pemahaman Mahasiswa Program Studi Pendidikan Bahasa Dan Sastra Indonesia Angkatan 2021 A Universitas Riau Terhadap Penulisan Arab Melayu - Hasnah Faizah; Syabrina Wahyudin; Cahaya Eka Juniarti; Karmila Karmila; Nazhifah Al-Adawiyah Tenrisau; Korinah Nurlaili (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
One of the skills that requires understanding is writing. Social life is never separated from activities that require writing. Writing even becomes a culture in a region such as the Malay land, one of which is Riau which has Arabic Malay writing. Malay Arabic which is a cultural treasure is preserved by the implementation of local content of Malay Arabic lessons from elementary school level. This study aims to determine the understanding of Indonesian Language and Literature Education Study Program Batch 2021 A Riau University Students towards Malay Arabic Writing. This research uses descriptive method with quantitative approach. Quantitative descriptive research method is a method that aims to create a picture or descriptive of a situation objectively using numbers, starting from data collection, interpretation of the data and the appearance and result. The results of the research showed that the understanding of Arabic Malay writing was good with a percentage of 90%, the ability to understand Arabic Malay writing was adequate with a percentage of 60%, and the ability to understand Arabic Malay writing was poor with a percentage of 50%. Overall, Indonesian Language and Literature Education Study Program students' understanding of Malay Arabic Writing is in the poor category with an average percentage of 67%.